Indicators of recovery for orange roughy (Hoplostethus atlanticus) in eastern Australian waters fished from 1987 - Kloser, Rudy; Sutton, C.; Krusic-Golub, K.; Ryan, T. (Elsevier BV, 2015)
© 2015 .Compared to an 18 year New Zealand study (. Clark et al., 2000) we found multiple signs of recovery for orange roughy in Australian waters. Orange roughy were listed as conservation dependent in Australian waters in 2006, with most stocks reported to be well below 20% of estimated pre-fishing equilibrium biomass and closed to targeted fishing. The largest known spawning aggregations occur on the east coast of Tasmania. This area has been fished and monitored since 1987. A specific monitoring programme was established in 2006 to determine whether and at what rate the spawning sites would rebuild. Acoustic biomass estimates were on average 1.5 times higher than that expected from a recent stock assessment and between 2006 and 2013 have shown an increasing then decreasing trend. Positive signs of a population recovery include an increased biomass at the spawning sites since fishing ceased, large change in the age structure of the population and a 74% increase in the reproductive potential of females since 1987. Given the late maturation of orange roughy entering the spawning biomass (~30 years) and the short duration of fishing (~26 years), these changes represent pre-fishing recruitment still entering the fishery. Biomass, age and length frequency data were variable between and within spawning sites; this complicates the use of a single or multiple spawning sites to monitor the exploitation and recovery of the fishery.